High outbreeding as a consequence of selfed ovule mortality and single vector bat pollination in the amazonian tree Pseudobombax munguba (Bombacaceae) - Gribel, Rogério; Gibbs, Peter Edward (International Journal of Plant Sciences, 2002)
The pollination biology and breeding system of Pseudobombax munguba, a tree species of the várzea of the Amazonian floodplain, was studied by field observations and hand pollinations using varying proportions of self and cross pollen. Progeny in sample fruits were tested for self or cross paternity using an isozyme genetic marker. Pseudobombax munguba has nocturnal, white, brushlike flowers that, surprisingly, lack nectar, and they are pollinated by a single, large bat species, Phyllostomus hastatus. Although self pollen tubes penetrated ovules with equal facility to cross tubes, fully selfed flowers failed to form fruits. Flowers with mixed (self + cross) pollinations set fewer fruits than those of full crosses, and the fruiting success decreased with self : cross pollen ratio (i.e., 1 : 1 vs. 3 : 1). Fruits from such mixed pollinations contained varying but generally low (mean 3.3%, range 0%-22%) numbers of selfed seed. We conclude that although P. munguba lacks a conventional stigmatic or stylar self-incompatibility mechanism, the combination of exclusive pollination by a wide-ranging bat vector and the death of most selfed ovules provide this species with a highly outcrossing mating system.
Keywords: Bat; Breeding; Pollination; Tree; Phyllostomus Hastatus; Pseudobombax Munguba